2012
DOI: 10.1051/0004-6361/201118303
|View full text |Cite
|
Sign up to set email alerts
|

Rotten Egg nebula: the magnetic field of a binary evolved star

Abstract: Context. Most of the planetary nebulae (PNe) observed are not spherical. The loss of spherical symmetry occurs somewhere between the asymptotic giant branch (AGB) phase and the PNe phase. The cause of this change of morphology is not yet well understood, but magnetic fields are one of the possible agents. The origin of the magnetic field remains to be determined, and potentially requires the presence of a massive companion to the AGB star. Therefore, further detections of the magnetic field around evolved star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The sequence of these processes results in the development of an optical depth gradient in the direction from the equator to the polar axis of the system. The presence of a companion and/or a magnetic field in the system may also prove to be the physical factor that causes the loss of the spherical symmetry of the stellar envelope during the short evolutionary interval between the AGB and post-AGB stages (see [116,117] and references therein). In their recent paper Koning et al [118] proposed a simple PPN model based on a pair of evacuated cavities inside a dense spherical halo.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The sequence of these processes results in the development of an optical depth gradient in the direction from the equator to the polar axis of the system. The presence of a companion and/or a magnetic field in the system may also prove to be the physical factor that causes the loss of the spherical symmetry of the stellar envelope during the short evolutionary interval between the AGB and post-AGB stages (see [116,117] and references therein). In their recent paper Koning et al [118] proposed a simple PPN model based on a pair of evacuated cavities inside a dense spherical halo.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Then the high resolution Very Long Baseline Array (VLBA) observations by Leal-Ferreira et al (2012), with a synthesised beam size of ∼1.7 × ∼0.9 mas, allowed the detection of 30 H2O masers. Only three spots exhibited linear polarisation, ranging from p=0.28% to p=1.15%.…”
Section: Combined Views Of the Magnetic Field In Oh 2318+42mentioning
confidence: 99%
“…Alves et al 2012;Amiri et al 2012;Leal-Ferreira et al 2012;Vlemmings et al 2011Vlemmings et al , 2006b). Both single-dish and interferometric observations have revealed that silicon monoxide (SiO), water (H 2 O), hydrogen cyanide (HCN), hydroxyl (OH), and methanol (CH 3 OH), among others, can naturally generate polarized maser emission in these enviroments (e.g.…”
Section: Introductionmentioning
confidence: 99%